Exploring University-Industry Collaboration for Innovation in Azerbaijan : The Case of ADA University - Jabrayilova, Mahin (ADA University, 2021)
This thesis explores the phenomenon of university-industry collaboration in Azerbaijan, using ADA University as a case study, along with the benefits and challenges of this collaboration. Moreover, it provides insights into the way universities approach students to foster their entrepreneurship skills. The study adopted a mixed-method research approach conducting semi-structured interviews with nine representatives of university and industry. At the same time, questionnaires with the participation of 111 senior students were conducted in this study. The findings reveal that the case university tries to improve collaboration with industry, and industry partners of this university are fully satisfied with this collaboration. There are benefits and possible challenges of this collaboration. Benefits of university-industry collaboration are cadre development , bringing industry’s problems to education program in the various subject areas, the preparation of students for different industries, fostering faculty and students’ research competencies, adding value to society with corporate social responsibility activities, improving competitiveness, respect and ethics in the workplaces, and adding economic and social value to the government. Besides benefits, there are challenges of university-industry collaboration in Azerbaijan. The main challenge is the lack of mutual interests between partners and slow professional communication. Another problem of this collaboration is the lack of the best practices to look and learn in the local context, having different social and economic values of the partners, problems regarding sponsorship and taxes in the later stages of collaboration, lack of tangible resources, and fluctuations in the economy. The study also shows that university-industry collaboration fosters students’ innovativeness with various activities such as sponsorship, training, corporate social responsibility projects, start-up competitions, and internships.
Keywords: Education